Duchowe piękno wdowieństwa ślubowanego Bogu na podstawie De bono viduitatis i Epistula 130 św. Augustyna - Jaśkiewicz, Sylwester (Vox Patrum, 2022)
The original contribution of the Bishop of Hippo to the formation of widows is the study of spiritual, internal beauty (pulchritudo spiritalis). It was perfectly harmonized with other indications addressed to them, especially in De bono viduitatis and Epistula 130, and is part of a much wider concept of the spiritual man (homo spirituals), which after 411 the Hipponese develops in an anti-Pelagian context. Although the widow's abstinence is a gift from God and prompts her to be grateful, it does not absolve her from the trouble of pleasing her Bridegroom. Since the great shepherd of the Church of Hippo was well aware that he should teach continence so that widows themselves would love it, he speaks of it and of all God-consecrated widowhood in terms of beauty and spiritual bliss. Yes, step by step, with unparalleled eloquence and skill, it traces the smallest elements of the spiritual beauty of violas viduarum.